High-Temperature Tribological Behavior of Al0.3Cr0.5Fe1.5Mn0.5Ni High-Entropy Alloys With Addition of Titanium and Carbon - Peng, Chun-Hao; Tsai, Che-Wei; Kuo, Chia-Ming; Chiu, Sheng-Min (Frontiers in Materials, 2022)
In this study, the Al0.3Cr0.5Fe1.5Mn0.5Ni high-entropy alloys (HEAs) with addition of titanium and carbon was prepared. The as-cast alloys were composed of FCC solid solution and TiC particles, and were further aged and strengthened by precipitation of B2-NiAl phase at 700 ℃ for 10 h to increase hardness from Hv 200 to Hv 400. Tribological properties of the HEAs and commercial tool steel (AISI M2) against Al2O3 under dry sliding condition at room-temperature and elevated temperatures are compared. After high-temperature wear testing, the HEAs demonstrated exceptional oxidation resistance and a lower friction coefficient than M2 steel since the dense glazed layer on the surface of the HEAs served as a lubricant to decrease the friction coefficient, and protected the substrate from oxidation.